Characterization of a common wheat (Triticum aestivum L.) TaSnRK2.7 gene involved in abiotic stress responses - Zhang, Hongying (Journal of experimental botany, 2011)
Sucrose non-fermenting-1-related protein kinase 2 (SnRK2) plays a key role in the plant stress signalling transduction pathway via phosphorylation. Here, a SnRK2 member of common wheat, TaSnRK2.7, was cloned and characterized. Southern blot analysis suggested that the common wheat genome contains three copies of TaSnRK2.7. Subcellular localization showed the presence of TaSnRK2.7 in the cell membrane, cytoplasm, and nucleus. Expression patterns revealed that TaSnRK2.7 is expressed strongly in roots, and responds to polyethylene glycol, NaCl, and cold stress, but not to abscisic acid (ABA) application, suggesting that TaSnRK2.7 might participate in non-ABA-dependent signal transduction pathways. TaSnRK2.7 was transferred to Arabidopsis under the control of the CaMV-35S promoter. Function analysis showed that TaSnRK2.7 is involved in carbohydrate metabolism, decreasing osmotic potential, enhancing photosystem II activity, and promoting root growth. Its overexpression results in enhanced tolerance to multi-abiotic stress. Therefore, TaSnRK2.7 is a multifunctional regulatory factor in plants, and has the potential to be utilized in transgenic breeding to improve abiotic stress tolerance in crop plants